HUBUNGAN PERILAKU IBU DENGAN STATUS PEMBERIAN KOLOSTRUM PADA BAYI DI LEMBAH LUBUK RAYA KABUPATEN TAPANULI SELATAN - siregar, Nurelilasari (Universitas Aufa Royhan, 2024)
Giving colostrum is one of the health problems caused by the lack of information received by pregnant women and breastfeeding mothers. The low level of giving colostrum is one of the triggers for the nutritional status of infants and toddlers. All babies need to receive colostrum to fight off an infection that is estimated to save one million infant lives. More than 90% of mothers discard colostrum and give solid food early. The purpose of this study was to determine the relationship between maternal behavior and the status of giving colostrum to infants in Lembah Lubuk Raya, South Tapanuli Regency. The type of research used was quantitative with a cross sectional study approach. The population and samples were all mothers who had babies in the Lembah Lubuk Raya Work Area as many as 41 people, with a sample using the total sample method. The analysis used is the Chi-square test. The results of the analysis showed that there was a relationship between mother's knowledge (p=0.000), mother's attitude (p=0.002), mother's actions (p=0.008), mother's behavior (p=0.008) with the status of giving colostrum to the baby. The conclusion is that the mother's behavior is related to the status of giving colostrum to the baby. Suggestions for mothers to be able to give colostrum to their babies as soon as possible, and to health workers to provide counseling about colostrum breastfeeding when mothers do prenatal check-ups.